Measures of Financial Capacity: A Review. (23rd May 2017) - Ghesquiere, Angela R; McAfee, Caitlin; Burnett, Jason
Abstract: Purpose of the Study: Capacity to manage finances and make financial decisions can affect risk for financial exploitation and is often the basis for legal determinations of conservatorship/guardianship. Several structured assessments of financial capacity have been developed, but have not been compared regarding their focus, validity, or reliability. Therefore, we conducted a review of financial capacity measures to examine these factors. Design and Methods: We searched electronic databases, reference lists in identified articles, conference proceedings and other grey literature for measures of financial capacity. We then extracted data on the length and domains of each measure, the population for which they were intended, and their validity and reliability. Results: We identified 10 structured measures of financial capacity. Most measures could be completed in 25–30 min, and were designed to be administered to older adults with some level of cognitive impairment. Reliability and validity were high for most. Implications: Measurement of financial capacity is complex and multidimensional. When selecting a measure of financial capacity, consideration should be made of the population of focus and the domains of capacity to be assessed. More work is needed on the cultural sensitivity of financial capacity measures, their acceptability, and their use in clinical work. Better understanding of when, and to whom, to administer different financial capacity measures could enhance the ability to accurately detect those suffering from impaired financial capacity, and prevent related negative outcomes like financial exploitation.